Ethnic-Cultural Bullying Among Adolescents: Key Insights from Global Evidence - Borrego-Ruiz, Alejandro (Cultural Conflict and Integration, 2025)
Ethnic-cultural bullying is based on perceived differences such as country of origin, cultural background, or skin color, and is rooted in broader dynamics of discrimination and social exclusion. However, despite the growing body of literature, its visibility and understanding remain relatively limited. This narrative review examines the current state of knowledge on ethnic-cultural bullying among adolescents, focusing on its defining features, associated factors, dynamics, and consequences. In addition, it places special emphasis on two underexplored associated areas of pivotal significance: humiliation as a potential key emotional outcome and digital technologies as a contextual amplifier of its occurrence and progression. Finally, this review also discusses the implications of these insights for the development of effective interventions and policy measures. Ethnic-cultural bullying constitutes a global phenomenon that is driven by explicit racial and cultural discrimination, involving both direct aggression and subtle exclusion. Protective factors such as empathy, teacher tolerance, and inclusive peer norms can reduce the risk, while migrant status and visible ethnic markers increase vulnerability. Victims of ethnic-cultural bullying often face stigma, secondary victimization, mental health issues, increased substance use, and higher suicide risk. Humiliation is an emotion closely related to bullying dynamics, but also a culturally charged phenomenon that perpetuates intergroup divisions and stigmatization. Digital technologies potentially contribute to increased dynamics of ethnic-cultural bullying, especially among minority youth. Effective interventions against ethnic-cultural bullying must be identity-aware and grounded in scientific evidence. Ultimately, comprehensive, intersectional, and culturally informed approaches are necessary to address its complex social and psychological impacts.